Treatment Toxicity in Elderly Patients With Advanced Non–Small Cell Lung Cancer. (October 2017) - Kale, Minal S.; Mhango, Grace; Gomez, Jorge E.; Sigel, Keith; Smith, Cardinale B.; Bonomi, Marcelo; Wisnivesky, Juan P.
Abstract : Objectives: Toxicity is a main concern limiting the use of chemotherapy and radiotherapy (RT) for elderly patients with non–small cell lung cancer (NSCLC). The objective of this study was to assess the rates of treatment-related toxicity among elderly stage IIIB and IV NSCLC patients. Materials and Methods: We used the Surveillance, Epidemiology, and End Results registry linked to Medicare records to identify 2596 stage IIIB and 14, 803 stage IV NSCLC patients aged 70 years and above, diagnosed in 2000 or later. We compared rates of toxicity requiring hospitalization according to treatment (chemotherapy, RT, or chemoradiation [CRT]) in unadjusted and adjusted models controlling for selection bias using propensity scores. Results: Among stage IIIB patients, rates of any severe toxicity were 10.1%, 23.8%, 30.4%, and 39.2% for patients who received no treatment, RT, chemotherapy alone, and CRT, respectively. In stage IV patients, rates of any severe toxicity were 31.5% versus 13.5% among those treated with and without chemotherapy, respectively. In stage IIIB patients treated with CRT, the most common toxicities was esophagitis (odds ratio, 48.5; 95% confidence interval, 6.7-350.5). Among stage IV patients treated with chemotherapy, the risk of toxicity was highest for neutropenia (odds ratio, 8.4; 95% confidence interval, 6.1-11.5). Conclusions: Toxicity was relatively common among stage IIIB patients with up to a 6-fold increase in elderly individuals treated with CRT and a 4-fold increase in toxicities among stage IV patients. This information should be helpful to guide discussions about the risk-benefit ratio of chemotherapy and RT in elderly patients with advanced NSCLC.